PENERAPAN PEMBELAJARAN INKLUSIF PAI: STRATEGI DAN UPAYA DALAM PEMAHAMAN TAUHID SISWA - Zarkiyah Herizon; Muhammad Arifin Rahmanto (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to analyze the implementation of inclusive learning in Islamic Religious Education (PAI) and teacher strategies in improving students’ understanding of monotheism at SMAN 23 Jakarta. Using a descriptive qualitative approach, data were collected through participatory classroom observation and in-depth interviews with Islamic Religious Education teachers and eleventh-grade students from diverse backgrounds. Data were analyzed through a systematic process of grouping, interpreting, and deriving meaning from field findings. Project-Based Learning and storytelling strategies have proven effective in strengthening understanding of monotheism values ​​and fostering tolerance. Despite facing constraints such as time constraints and a lack of continuity of teaching between levels, teachers were able to create an adaptive and empathetic learning atmosphere. The novelty of this study lies in the integration of monotheism values ​​through an inclusive approach that aligns with the 4th Sustainable Development Goal of the SDGs concerning quality education.